Van Gulik's The Lore of the Chinese Lute Revisited*. Issue 1 (31st May 2017) - Xiao, Ouyang
Abstract : In this article I propose a critical examination of van Gulik's The Lore of the Chinese Lute (LCL) in respect to its bibliographical sources and consequent aesthetic contentions. Despite being arguably the first academic monograph on the ideology of qin and historically a major non-Chinese source for the study of qin in general, the LCL does not represent van Gulik's mature thinking on qin . The LCL is limited by objective circumstances surrounding its writing and flaws in van Gulik's bibliographical engagement. His study of the musicology of Yueji on the basis of inaccurate translation and a neglect of the Neo-Confucian reading of Yueji, his hypothesis of Daoist dominance and Buddhist or Indian influence in the practice of qin with mistaken evidence, his skepticism of the truth of the literati tradition with fundamental bibliographical flaws, all require reconsideration. The current lacuna in the critical investigation of the LCL not only urges contemporary researchers to continue where van Gulik left off, but also calls for new research projects on qin and Chinese literati music in general.